2014
DOI: 10.1074/jbc.m113.511444
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Modulate the Transcriptional Regulation of Guanylyl Cyclase/Natriuretic Peptide Receptor-A Gene

Abstract: Background: Natriuretic peptide receptor-A (NPRA) lowers blood pressure and blood volume. Results: Data show that histone deacetylase inhibitors (HDACi) enhance NPRA expression by blocking HDACs and interacting with Sp1, histone acetyltransferase, and acetylated histones. Conclusion: Results suggest that epigenetic mechanisms regulate NPRA gene transcription. Significance: Findings will help to identify molecular targets regulating NPRA expression and function in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…Indeed, both HNF4a and SP1, besides transcriptional activation, also have been shown to function as transcriptional repressors in a cell type, stimulus, and gene-specific manner. 35,46,47 Taken together, the data indicate that in hepatocytes ethanol treatment can influence the function of HNF4a and SP1, leading to a transition from transcriptional activators to repressors that underlie ethanol-induced down-regulation of CPT-1A gene expression.…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, both HNF4a and SP1, besides transcriptional activation, also have been shown to function as transcriptional repressors in a cell type, stimulus, and gene-specific manner. 35,46,47 Taken together, the data indicate that in hepatocytes ethanol treatment can influence the function of HNF4a and SP1, leading to a transition from transcriptional activators to repressors that underlie ethanol-induced down-regulation of CPT-1A gene expression.…”
Section: Discussionmentioning
confidence: 77%
“…Promoter region of the GC-A gene contains three potential Sp1-binding sites and their involvement in gene activation has been demonstrated (Liang et al, 1999;Garg et al, 2002). A few reports have shown that the Sp1 protein is involved in activation of the GC-A gene (Liang et al, 2001;Kumar et al, 2014). However, mechanisms of Sp1-mediated activation of the GC-A gene in different cell types remain unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Primary antibodies against δEF1 (catalog number sc‐10573), pSmad2/3 (Ser423/425; catalog number sc‐11769), H1 (catalog number sc‐10806), α‐SMA (catalog number Sc‐56499), COL1A2 (catalog number sc‐8788) and β‐actin (catalog number Sc‐47778 HRP) were purchased from Santa Cruz Biotechnology Inc. (Santa Cruz, CA, USA). Primary antibody for NPRA was produced as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…The 5′ flanking region (~ 500 bp upstream of the start codon) of the Npr1 gene (encoding GC‐A/NPRA) contains binding sites for several known transcription factors, and appears to play a critical role in functional regulation and expression of this gene . Previous studies from our laboratory and by others have focused on the regulation of Npr1 gene expression and function, however, the complete molecular machinery regulating its expression and function is yet to be established .…”
Section: Introductionmentioning
confidence: 99%